Penyelesaian Sengketa Pemilihan Kepala Desa Serentak di Kabupaten Situbondo - Faizin, Nurul; Ubaidillah, Lutfian (Indonesian Journal Publisher, 2023)
During the simultaneous village elections, there are several problems which we usually call village head election disputes. In the case of village head election disputes, it is not explicitly regulated regarding the process of resolving disputes over village head election results, either in Law Number 6 of 2014 concerning Villages, Government Regulation Number 43 of 2014 Regarding Village Implementing Regulations Minister of Home Affairs Regulation Number 72 of 2020 concerning Election of Village Heads Regional Regulation Number 9 of 2015 concerning Villages, Regent Regulation Number 19 of 2019 concerning Implementing Regulations of Situbondo Regency Regional Regulations Number 9 of 2015 concerning Village Heads. The aim of this writing is to find out the mechanism for resolving disputes over the election of village heads in Situbondo Regency is in accordance with Law Number 6 of 2014 concerning Villages. This type of research is normative juridical research which aims to provide an overview and explanation or consider and formulate the problem of comparing theories and legal norms contained therein. Mechanisms and dispute resolution have been regulated in Articles 61 and 62 of Regional Regulation number 9 of 2015 concerning village heads, which are further technically implemented in Articles 55 and 56 of Situbondo Regency Regulation Number 19 of 2019 Regulations for Implementing Situbondo Regency Regional Regulation Number 9 of 2015 concerning Village Heads. Basically, these regulations are in accordance and refer to Article 37 paragraph (6) of the Village Law, Article 41 paragraph (7) PP Number 43 2014, and Article 44 paragraph (3) Minister of Home Affairs Regulation Number 72 of 2020.